Peningkatan kemampuan guru dalam menerapkan model pembelajaran melalui kegiatan supervisi kelas MIN 13 Aceh Barat Daya - warni, Warni (Universitas Serambi Mekkah, 2020)
making use of learning models that are appropriate with the learning material. In general, teachers rarely use the learning model in each learning process, due to the lack of teacher understanding of learning models that can facilitate teachers in implementing the learning process in class. Actually there are many learning models that can be used by every teacher in the learning process. By using appropriate learning models, of course students will be motivated in learning, and this will have a positive impact on learning outcomes. The main problem in research, namely